1995
DOI: 10.1152/jn.1995.73.6.2568
|View full text |Cite
|
Sign up to set email alerts
|

EMG analysis of harmaline-induced tremor in normal and three strains of mutant mice with Purkinje cell degeneration and the role of the inferior olive

Abstract: 1. The effects of intraperitoneal injections of 10 mg/kg harmaline were tested in normal mice and three strains of cerebellar mutant mice with Purkinje cell degeneration. Ten normal (wild-type) mice (+/+), as well as five lurcher (lc/+), six nervous (nr/nr), and eight Purkinje cell degeneration (pcd/pcd) mutants were implanted with chronic electromyogram (EMG) electrodes in the hamstring and quadriceps muscle groups of the right hindlimb. 2. EMGs were recorded in each of the mice during spontaneous activity be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
45
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 26 publications
6
45
0
Order By: Relevance
“…Harmaline-treated animals demonstrate synchronous, rhythmic bursts of activity (8 -12 Hz) throughout the spinocerebellar system, including inferior olive, Purkinje cells, deep cerebellar nuclei, reticular formation, and motoneurons (Lamarre and Mercier, 1971;Lamarre and Weiss, 1973;LlinĂĄs and Volkind, 1973). Bursts of rhythmic neuronal activity are time-locked to the harmaline-induced tremor, as assessed by electromyographic recording (De Montigny and Lamarre, 1973;Milner et al, 1995). These data indicate that the tremor is induced by rhythmic activation of motoneurons attributable to entrainment of brainstem descending pathways by the olivocerebellar rhythm.…”
Section: Discussionmentioning
confidence: 75%
“…Harmaline-treated animals demonstrate synchronous, rhythmic bursts of activity (8 -12 Hz) throughout the spinocerebellar system, including inferior olive, Purkinje cells, deep cerebellar nuclei, reticular formation, and motoneurons (Lamarre and Mercier, 1971;Lamarre and Weiss, 1973;LlinĂĄs and Volkind, 1973). Bursts of rhythmic neuronal activity are time-locked to the harmaline-induced tremor, as assessed by electromyographic recording (De Montigny and Lamarre, 1973;Milner et al, 1995). These data indicate that the tremor is induced by rhythmic activation of motoneurons attributable to entrainment of brainstem descending pathways by the olivocerebellar rhythm.…”
Section: Discussionmentioning
confidence: 75%
“…The ÎČ-carboline alkaloid tremor shares many features with ET. These include several of the principal clinical features (e.g., tremor frequency and electromyographic characteristics of the tremor) and drugresponse characteristics (pharmacological responsiveness to benzodiazepines, alcohol, and barbiturates) (Cross et al, 1993;Fuentes and Longo, 1971;Milner et al, 1995;Rappaport et al, 1984;Sinton et al, 1989;Trouvin et al, 1987). Also, underlying brain changes are similar.…”
Section: Discussionmentioning
confidence: 99%
“…Changes, including neuronal loss, have been shown to occur in the ET cerebellum (Axelrad JE, 2007 In Press; Louis et al, 2002a;Louis et al, 2004;Louis et al, 2006a;Louis et al, 2006b;Pagan et al, 2003;Shill H, 2007). Similarly, ÎČ-carboline alkaloids produce toxic damage with significant loss of cerebellar Purkinje cells (Du et al, 1997;Milner et al, 1995;O'Hearn and Molliver, 1997;Robertson, 1980;Sinton et al, 1989). While ÎČ-carboline alkaloids are produced endogenously in the human body (Gearhart et al, 2000;Wakabayashi et al, 1997), one study estimated that dietary sources were fifty times greater than endogenous sources (Pfau and Skog, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…12,13 BCA-induced tremor shares many features with ET including its principal clinical features, drug-response characteristics, [14][15][16][17][18][19] and underlying brain changes (cerebellar changes have been noted in physiologic and imaging studies of patients with ET; similarly, BCAs damage olivary-cerebellar pathways). 10,14,18,[20][21][22][23] The etiology of ET is poorly understood 24 and a better understanding of disease etiology and mechanisms has the potential to modify or prevent a disorder that affects as much as 4% of the adult population. 25 We previously demonstrated that blood concentrations of the BCA harmane were elevated in patients with ET vs controls.…”
mentioning
confidence: 99%